2009
DOI: 10.1016/j.ajhg.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding Mutations of HGF Are Associated with Nonsyndromic Hearing Loss, DFNB39

Abstract: A gene causing autosomal-recessive, nonsyndromic hearing loss, DFNB39, was previously mapped to an 18 Mb interval on chromosome 7q11.22-q21.12. We mapped an additional 40 consanguineous families segregating nonsyndromic hearing loss to the DFNB39 locus and refined the obligate interval to 1.2 Mb. The coding regions of all genes in this interval were sequenced, and no missense, nonsense, or frameshift mutations were found. We sequenced the noncoding sequences of genes, as well as noncoding genes, and found thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 79 publications
2
106
0
1
Order By: Relevance
“…The other variants that were also present in the sequencing dataset were communicated for the c.418A>C variant but limited to the DFNA4 region [Zheng et al, 2011]. One of the consequences of broadly screening large subsets of genes, as in the case of clinical and whole exomes, is the generation of large numbers of variants that require interpretation including synonymous variants, which could impact splice sites [Schultz et al, 2009;Wang et al, 2015]. It is common for even healthy individuals to carry private pathogenic mutations complicating the understanding of disease causing mutations [Jang et al, 2015].…”
Section: Interpretation Of the Mutation Compared To Already Detected mentioning
confidence: 99%
“…The other variants that were also present in the sequencing dataset were communicated for the c.418A>C variant but limited to the DFNA4 region [Zheng et al, 2011]. One of the consequences of broadly screening large subsets of genes, as in the case of clinical and whole exomes, is the generation of large numbers of variants that require interpretation including synonymous variants, which could impact splice sites [Schultz et al, 2009;Wang et al, 2015]. It is common for even healthy individuals to carry private pathogenic mutations complicating the understanding of disease causing mutations [Jang et al, 2015].…”
Section: Interpretation Of the Mutation Compared To Already Detected mentioning
confidence: 99%
“…By E13.5, reporter expression was found throughout the otic lines are used. The most commonly used line is the depending on the strength of the fluorescent reporter COX ET.AL: Conditional Gene Expression in the Mouse Inner Ear Using Cre-loxP Pirvola et al 2002;Arnold et al 2006;Zelarayan et al 2007;Barrionuevo et al 2008;Jones et al 2008;Rickheit et al 2008;Grimsley-Myers et al 2009;Schultz et al 2009;Wang et al 2009;Yamamoto et al 2009;Deng et al 2010;Freyer and Morrow 2010;Haugas et al 2010;Hurd et al 2010;Hwang et al 2010;Sipe and Lu 2011 (Hebert and McConnell 2000), which has been reported to cause haploinsufficiency phenotypes that include proliferation in other organs (Shen et al 2006;Eagleson et al 2007;Siegenthaler et al 2008). However, no change in proliferation in the inner ear has been reported in several papers where proper controls of Foxg1-Cre mice (without the floxed allele) were used (Yamamoto et al 2009(Yamamoto et al , 2011Hartman et al 2010;Brown and Epstein 2011).…”
Section: Cre/creer Lines For the Developing Otic Vesicle And Otocystmentioning
confidence: 99%
“…Although already seven ARNSHI loci have been mapped to chromosome 7 for which three genes have been identified, SLC26A5 [1] (MIM 60493), SLC26A4 [2] (MIM 605646) and HGF [3] (MIM 142409), there is no overlap between this new locus and previously reported loci.…”
Section: Introductionmentioning
confidence: 70%
“…3 ). For these ARNSHI loci, only the genes SLC26A5 for DFNB61 [1] , SLC26A4 for DFNB4 [2] and HGF for DFNB39 [3] have been identified. Additionally, on chromosome 7p lies the autosomal dominant (AD) locus DFNA5, which is centromeric to DFNB90 by 4.4 Mb, and on chromosome 7q is DFNA50 [19] , which lies between DFNB17 and DFNB13.…”
Section: Discussionmentioning
confidence: 99%